Funicular Myelosis in a Butcher: It Was the Cream Cans - Fabian Wolpert; Krisztina Baráth; Janis Brakowski; Roland Renzel; Michael Linnebank; Andreas R. Gantenbein (Case Reports in Neurological Medicine)
Background. Funicular myelosis is a known consequence of exposure to nitrous oxide. Nevertheless, there are only a few clinical trials assessing its long-term effects and there is no literature about the role of nutritional vitamin B12 supplementation in the context of nitrous oxide abuse. Case Descriptions. We diagnosed funicular myelosis in a young butcher, who consumed high amounts of meat regularly. Since the diagnostic process did not reveal any metabolic causes, reinterrogation of the patient uncovered recreational abuse of nitrous oxide out of whipped cream can gas cartridges. After stopping abuse and supplementation of vitamin B12, the patient recovered almost completely. Conclusions. In our case, even high nutritional vitamin B12 uptake could not compensate the noxious effects of nitrous oxide. Since there are emerging reports of increasing misuse, this should be considered in the diagnostic and therapeutic care of patients with nitrous oxide abuse. Furthermore, our case emphasizes that patients with vitamin B12 deficiency should be assessed for nitrous oxide abuse.